Penggunaan Bahasa Rungus dalam Kalangan Generasi Baru (Remaja) Masyarakat Rungus di Matunggong, Sabah The use of Rungus Language among the New Genaration (Youth) of Rungus in Matunggong, Sabah - Romzi Ationg; Andreas Totu; Chelster S. Pudin; Raymond Majumah (Penerbit Akademi Baru, 2018)
Various efforts have been made by authorities to ensure modernization occurs among Rungus tribes in Sabah, particularly in Matunggong. However, the efforts to modernize the Rungus tribe in Matunggong have made a negative impact on the use of native language. This study focuses on the current phenomenon, namely the decreasing use of Rungus language among the new generation of Rungus ethic itself. This study also aims to find out the level of the language used, the effects of this phenomenon if and the factors of this phenomena. The data of this study are collected using a mixedmethod approach. Through the analysis of the data obtained, it is found that the lethargy phenomenon has happened among the new generation of Rungus ethnic in Matunggong. This has led the Rungus Ethnic to face the possibility of their native language to become extinct. Modernisation is identified as the main factor contributing to this phenomenon, particularly the widespread use of national and international languages for modenisation purposes, the negative perceptions of their own native language, intermarriage, parental and peer roles and other modernisation factors. In accordance, some suggestions were raised to avoid the lethargy phenomenon by using the native language among the new generation of Rungus ethnic from happening.